The effects of coaches' emotional expressions on players' performance: Experimental evidence in a football context - Moll, T.; Davies, G. L. (Psychology of Sport and Exercise, 2021)
Objectives: Across two experiments, we examined the effects of coaches' nonverbal expressions of pride, shame, and happiness on players' emotions and performance. Design: Both experiments employed a between (emotional expression manipulation) within (pre- and post-manipulation) subjects design. Method: An expert male football coach was scripted to deliver performance feedback randomly displaying a specified emotion to skilled players who had just performed a passing test. In Experiment 1 (n = 28), players' actual coach displayed pride or shame. In Experiment 2 (n = 60), a confederate displayed pride, shame, happiness, or a neutral expression. Players then performed the passing test for a second time. In both experiments, players reported their emotions and perceptions of the coach. Results: The results showed that coaches' emotional expressions influenced players' emotions especially when players held a close relationship with the coach. Regardless, coaches' display of pride and happiness benefitted players' performance while the display of shame did not. Conclusion: These findings provide the first experimental evidence for the effects of coaches' emotional expressions on players' emotions and performance. These findings have important practical implications and advance the literature on how coaches' emotional expressions may influence players' emotions and performance.